Konsep Pendidikan Anak dalam Al-QurAn Surah Luqman Ayat 13-19 Perspektif Syekh Syarawi dalam Tafsir Asy Syarawi - Mardhiyah Agung Wahyuningsih; Tanfirul Khoiri (Universitas Syiah Kuala, 2025)
Islamic education is all conscious and deliberate efforts made by adults to lead and influence the physical and spiritual development of students in accordance with Islamic teachings towards the formation of a good personality. One of the references in Islamic education, especially child education, is Surah Luqman verses 13-19. The concepts, methods, stages of learning and the purpose of Islamic learning contained in the surah are described in detail in Tafsir Ash Sya'rawi. This paper will discuss Shaykh Sya'rawi's perspective on education.